A comparison of graphic characteristics of drawing a family, attachment disorders, and parental parenting styles in anxious and normal girl children - Mahnaz Sheikh; Mahvash Raghibi; Hanieh Sheikh (Journal of Research & Health, 2019)
Anxiety is the most prevalent psychiatric disorder in childhood which affects various aspects of children’s lives. This study aimed to compare graphic characteristics of drawing a family, attachment disorders, and parental parenting styles in anxious and normal girl children. This was a causal-comparative study. Its statistical population included all girl children aged 5 to 8 years old who were studying in kindergartens and elementary schools of Zahedan in 2015-16 and their parents. 50 children with anxiety disorders and 50 normal children were randomly selected as the sample. The tools were the Baumrind parenting style test, the Randolph attachment disorder questionnaire, and the draw-a-family Test. The data were analyzed by the chi-square and multivariate analysis of variance and the graphical characteristics of the children’s drawings were evaluated using the draw-a-family test. The results indicated that considering the graphic characteristics of the children’s drawings, there was a significant difference between the anxious and normal children and with regard to attachment disorders, there was a significant difference in terms of bullying at 0.99 confidence level. No significant difference was found between the anxious and normal children considering their parents’ parenting styles. Overall, it can be inferred that drawing a family can be used as a proper method to detect children’s family and emotional issues and to protect them from mental disorders.